'Becoming more confident in being themselves': The value of cultural and creative engagement for young people in foster care – Dawn Mannay, Phil Smith, Catt Turney, Stephen Jennings and Peter Davies. (May 2022) - Mannay, Dawn; Smith, Phil; Turney, Catherine; Jennings, Stephen; Davies, Peter Henry
There is evidence that engagement with the arts can engender transformative effects on young people's views of themselves and their futures, this can be particularly useful for children and young people in care. This paper draws on a case study of an arts-based programme delivered in Wales, UK. Field observations of the arts-based sessions were conducted, and the participant sample included young people in foster care (n = 8), foster carers (n = 7) and project facilitators (n = 3). The study employed interviews, observations, reflexive diaries, and metaphor work to explore the subjective accounts of these different stakeholders. This provided an insight into their experience of being involved with the arts-based programme, the impacts of this involvement, and what steps they felt could be taken to improve the model. The paper argues that arts and cultural engagement can be transformative in improving the confidence and social connectedness of young people in foster care, but that attention needs to be given to how programmes are delivered. The paper documents the often overlooked mundane, yet important, aspects of planning arts-based programmes, exploring the involvement of foster carers, interpersonal relationships, and the provision of refreshments. It calls for investment in developing carefully designed extracurricular opportunities for young people in care, where they can experience 'becoming more confident in being themselves'.